Pendidikan Karakter Perspektif Al-Qur’an - Sulaiman, Sulaiman (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2019)
Character education has become the focus of attention lately because of a setback that has resulted in moral decline. In the Qur'an, characters use the term "morality" which is interpreted as a habit that is accustomed. Will and habits generate strength. If the habit of producing a good deed is called akhlakul karimah. Character education is efforts that are designed and carried out systematically to help students understand the values of human behavior that are related to God, oneself, fellow human beings, the environment, and nationality which manifests in thoughts, attitudes, feelings, words, and actions based on religious norms, law, manners, culture, and customs. This paper aims to understand the formulation of the concept of Al-Quran perspective education. Through a textual and contextual understanding. Some of the concepts of character education that can be revealed from the Koran are character education in the Qur'an.